Reinforcement of multiwalled carbon nanotubesnatural rubber nanocomposite prepared by latex technology - Abd. Aziz Azira, Abang Ismawi Hassim Dayang Habibah, A. B. Suriani, Mahmood Mohamad Rusop (N/A, 2012)
Reinforcement of multiwalled carbon nanotubesnatural rubber nanocomposite prepared by latex technology by Abd. Aziz Azira, Abang Ismawi Hassim Dayang Habibah, A. B. Suriani, Mahmood Mohamad Rusop,